Analisis Persediaan Bahan Material Aspal Menggunakan Alat Stone Crusher dengan Metode RCCP - Mahmud, Gustamin; Saputra, Arie (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
PT Wirataco Mitra Mulia (WMM) is a company engaged in the construction of stone crushers such as split , medium , and stone ash. Problems that often occur in general in this company, one of which is not meeting the demands of consumers, where production supplies do not meet the demands of consumers. The purpose of this study was to analyze the inventory of asphalt materials at PT. Wirataco Mita Mulia. RCCP is a method used to analyze production inventory capacity in meeting production demand capacity needs while making a master production schedule (JIP), calculating efficiency, and calculating utility. Machine capacity 1 working day 8 hours and 1 work shift, 1 week = 6 working days, 1 month = 24 working days. Available time per month = 24 working days. The comparison made after the research shows that the split demand capacity = 10560 M3 while the available capacity = 14668 M3. Medium demand capacity = 7447, while available capacity = 13979 M3. For rock ash demand capacity = 7092 M3 while available capacity = 3416 M3, it means that the split and medium inventory capacities are met. Meanwhile, the demand for rock ash production was not met. For this reason, the company should carry out production planning based on the master production schedule and RCCP, so that the supply of rock ash can be fulfilled.